Synthesis and antimicrobial activity of some ester functionalized isoxazoles incorporating anthracene moieties via nucleophilic substitution reaction - M. Ahmed, Sarbast; Omer Ahmed, Hewa; H. S. Hussain, Faiq; Sardar Abdulrahman, Hayman; A. Qader, Hemn (Zanco Journal of Medical Sciences (ZJMS), 2023)
Background and objective: Five-membered heterocycle compounds having single oxygen and nitrogen atom at adjacent positions are known as isoxazoles. Isoxazole compounds have a broad range of biological activities and therapeutic value. In view of a strategic design of antimicrobial compounds, several new ester-functionalized isoxazoles were synthesized and characterized. Methods: A regioselective isoxazole incorporating an anthracene moiety was adducted via an effective 1,3-dipolar cycloaddition between anthracene nitrile oxide and propargyl bromide as a dipolarophile. Results: Synthesized isoxazole 4 underwent nucleophilic substitution reaction to produce unprecedented ester-functionalized isoxazoles 6a-j, by condensation with equimolar amounts of different generated in situ sodium carboxylate upon dissolving in acetonitrile with refluxing. The chemical structure of all target compounds was proved by (FT-IR, 1H-NMR, and APT13C-NMR) techniques and their antibacterial and antifungal activities was evaluated. Conclusion: Allnewly synthesizedcompounds6 a-j have been obtained in good yields after purification by column chromatography. They showed significant antibacterial and antifungal activity after screening against two bacterial strains, Escherichia coli and Staphylococcus aureus and a fungi strain, Candida albicans, using disc diffusion method.